GAMBARAN EFIKASI DIRI DAN PEAK EXPIRATORY FLOW RATE PASIEN PENYAKIT PARU OBSTRUKSI KRONIS (PPOK) - Suprayitno, Emdat; Khoiriyati, Azizah; Hidayati, Titiek (Pusat Penelitian dan Pengabdian kepada Masyarakat FKes Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Chronic Obstructive Pulmonary Disease (COPD) has become a huge public health problem in the world. In Asy-Syaafi Hospital, COPD is the most commonly found disease after bcronchitis among the patients in out patient unit of lung desease. Self efficacy showed patients’ confidence in independently managing chronic desease Wheter they want or not to start the treatment is determined by their self efficacy. Peak expiratory flow rate showed the condition and problems of lung function and the narrowing or blockage of the airway. Objective: To identify the conditions and problems of self efficacy and Peak expiratory flow rate in COPD patients in Asy-Syaafi Hospital Pamekasan, East Java. Method: This research was descriptive study used non analytic cross sectional design, with total sampling, involving 30 respondents. Data were collected with a questionnaire of the COPD self efficacy (CSES) and peak flow meter. Results: Self  efficacy was in low category with score less than 99 (86.7%) and Peak expiratory flow rate was less than <50% of the PEF (90%). Conclusion: Most of  COPD Self efficacy in Asy-Syaafi Hospital Pamekasan were not good category and Peak expiratory flow rate contained in red zone or the occurrence of major constriction of the airways.   Keywords: COPD, Self Eficacy, Peak Expiratory Flow Rate